Preparation method and application of activated carbon loaded nano zero-valent copper material

By loading nano zero-valent copper on activated carbon, the problem of low adsorption capacity of activated carbon under high humidity is solved, and the adsorption performance to foul-odor gases is significantly improved, especially hydrogen sulfide and toluene, achieving efficient adsorption effect.

CN119281294APending Publication Date: 2025-01-10ACADEMY OF MILITARY MEDICAL SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411410967.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing activated carbon has low adsorption capacity to foul-odor gases in high humidity environments, especially hydrogen sulfide and toluene, which is difficult to effectively remove.

Method used

By loading nano zero-valent copper on activated carbon, activated carbon-loaded nano zero-valent copper materials are prepared, pretreated with sulfuric acid solution and deionized water, and the agglomeration of nanometal particles is prevented by stirring, washing, and drying, thereby enhancing adsorption performance .

Benefits of technology

Under high humidity conditions, the adsorption capacity of foul-odor gases is significantly improved, especially the adsorption capacity of hydrogen sulfide and toluene is maintained, and the preparation process is simple and low, and there is no secondary pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281294A_ABST
    Figure CN119281294A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of gas adsorbents. The invention provides a preparation method and application of an activated carbon loaded nano zero-valent copper material, firstly, activated carbon is pretreated and placed in deionized water for ultrasonic treatment to obtain a solid-liquid mixture, then a copper sulfate solution and a potassium borohydride solution are dropwise added into the solid-liquid mixture at the same time, reaction is performed until no obvious bubbles are generated in system liquid, and the activated carbon loaded nano zero-valent copper material is obtained; and the modified activated carbon material is cleaned for multiple times and freeze-dried to obtain the activated carbon loaded nano zero-valent copper material, wherein argon protection is needed in the reaction process. The activated carbon loaded nano zero-valent copper material prepared by the method still keeps relatively high adsorption performance in a high-humidity environment, especially for adsorption of methylbenzene and hydrogen sulfide gas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of gas adsorbents, and in particular to a preparation method and application of an activated carbon-loaded nanometer zero-valent copper material. Background Art

[0002] The National Standard of the People's Republic of China, "Emission Standard of Odor Pollutants" (GB-14554-93), stipulates that malodor refers to any odor that stimulates the olfactory organ and causes people to feel unpleasant and damages the living environment. Malodorous gases are usually mixed gases with low concentration components. When a certain malodorous component reaches its olfactory threshold concentration, people will smell the corresponding malodor. Malodorous substances contain an atomic group in their molecular structure, called a "stinking group", which is also the main cause of malodor. Malodorous pollutants are harmful to the human respiratory system, circulatory system, digestive system, endocrine system and nervous system.

[0003] Existing treatment technologies are mainly divided into three categories: physical methods, chemical methods, and biological methods. Due to its simplicity, wide application range, and low cost, adsorption is currently the most commonly used method for odor gas treatment. Therefore, finding the best adsorbent is crucial for the commercial application of adsorption technology.

[0004] Activated carbon materials are widely used for the adsorption and recovery of most types of malodorous gases. The adsorption capacity of activated carbon for malodorous gases ranges from ten milligrams per gram to several hundred milligrams per gram, which depends on the physical and chemical properties of the activated carbon, such as specific surface area, pore size, pore volume, chemical functional groups, etc.; it is also related to the properties of the malodorous gas itself, such as molecular size and polarity; it is also related to the adsorption conditions, such as temperature, relative humidity, concentration, gas flow rate, etc. Due to its large surface area and rich pore structure, activated carbon has a strong adsorption capacity for malodorous gases. At the same time, the rich chemical functional groups on the surface of activated carbon enable it to produce good chemical adsorption for malodorous gases. However, due to the poor selectivity of activated carbon for adsorbents, in the treatment of high-humidity malodorous gases, the adsorption capacity of the target pollutants is often reduced because water vapor occupies most of the adsorption sites, especially when the relative humidity exceeds 60%, most activated carbons have a very low adsorption capacity for malodorous gases.

[0005] Therefore, it is crucial to develop an activated carbon material that can adsorb a variety of odorous gases under high humidity conditions. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a preparation method and application of activated carbon-loaded nano zero-valent copper material. By designing the process conditions of its preparation process, activated carbon loaded with nano zero-valent copper metal can be obtained accordingly, which effectively prevents the agglomeration of nano metal particles, and is therefore suitable for removing malodorous gases in high humidity environments, especially malodorous gases such as hydrogen sulfide and toluene.

[0007] In order to achieve the above object, one of the objects of the present invention is to provide a method for preparing an activated carbon-supported nano zero-valent copper material, comprising:

[0008] S1, pretreating activated carbon with sulfuric acid solution and deionized water to obtain pretreated activated carbon powder;

[0009] S2, stirring the pretreated activated carbon powder and deionized water to obtain an activated carbon deionized water mixed solution;

[0010] S3, using CuSO 4 ·5H 2 O.KBH 4 and deionized water, stirring the activated carbon deionized water mixed solution to obtain an activated carbon zero-valent copper mixed solution;

[0011] S4, using deoxygenated water, anhydrous ethanol and a vacuum freeze dryer, the activated carbon zero-valent copper mixed solution is washed, pre-frozen and dried in sequence to obtain the activated carbon-loaded nano zero-valent copper material.

[0012] Furthermore, the method of pretreating the activated carbon with a sulfuric acid solution and obtaining the pretreated activated carbon powder after drying comprises:

[0013] S11, grinding the activated carbon into powder, and adding the powder into a sulfuric acid solution for soaking treatment to obtain soaked activated carbon;

[0014] S12, using deionized water to wash and dry the soaked activated carbon to obtain pretreated activated carbon powder.

[0015] Furthermore, the activated carbon powder is 8 mesh to 50 mesh.

[0016] Furthermore, the concentration of the sulfuric acid solution is 0.01 mol / L to 0.5 mol / L; and the soaking time is 10 min to 20 min.

[0017] Furthermore, the use of CuSO 4 ·5H 2 O.KBH 4 , deionized water and a peristaltic pump, stirring the activated carbon deionized water mixed solution to obtain an activated carbon zero-valent copper mixed solution, comprising:

[0018] S31, CuSO 4 ·5H 2 O and KBH 4 Add to deionized water and adjust the volume to 100ml-250ml to obtain CuSO 4 ·5H 2 O-KBH 4 Mixing solutions;

[0019] S32, under room temperature and anaerobic conditions, using a peristaltic pump, dropwise adding the CuSO 4 ·5H 2 O-KBH 4 The solutions are mixed and stirred to obtain an activated carbon zero-valent copper mixed solution.

[0020] Furthermore, the KBH 4 CuSO 4 ·5H 2 The molar ratio of O is 3:1 to 6:1; the dropping speed of the peristaltic pump is 1.5 ml / min to 2 ml / min; and the stirring speed is 300 r / min to 350 r / min.

[0021] Furthermore, the activated carbon-zero-valent copper mixed solution is sequentially washed, pre-frozen, and dried using deoxygenated water, anhydrous ethanol, and a vacuum freeze dryer to obtain the activated carbon-loaded nano-zero-valent copper material, comprising:

[0022] S41, using deoxygenated water and anhydrous ethanol to wash the activated carbon-supported nano zero-valent copper material in sequence to obtain a washed activated carbon-supported nano zero-valent copper material;

[0023] S42, pre-freezing the washed activated carbon-loaded nano zero-valent copper material to obtain a pre-frozen activated carbon-loaded nano zero-valent copper material;

[0024] S43, using a vacuum freeze dryer to dry the pre-frozen activated carbon-loaded nano zero-valent copper material to obtain the activated carbon-loaded nano zero-valent copper material.

[0025] Furthermore, the mass loading ratio of the nano-zero-valent copper in the activated carbon-loaded nano-zero-valent copper material on the activated carbon is 5wt.% to 20wt.%; the average particle size of the loaded nano-zero-valent copper is 100nm to 250nm;

[0026] Preferably, the mass loading ratio of nano zero-valent copper on the activated carbon is 5wt.% to 15wt.%.

[0027] The second purpose of the present invention is to provide an application of activated carbon-loaded nano zero-valent copper material, especially in the adsorption of malodorous gases under high humidity conditions.

[0028] Furthermore, the high humidity is 0-80%; the malodorous gas is one or two of hydrogen sulfide and toluene.

[0029] The beneficial effect of the present invention is that, compared with the prior art, it provides a preparation method and application of an activated carbon-loaded nano zero-valent copper material.

[0030] The present invention utilizes the advantages of large specific surface area and high porosity of activated carbon materials to load nano zero-valent copper on activated carbon, which can not only avoid the agglomeration of nanoparticles, but also enhance the adsorption capacity of activated carbon for malodorous gases in high humidity environments. The preparation process of the present invention is simple and easy to scale up, the raw materials used are cheap and easy to obtain, and there is no secondary pollution, so it has good application prospects. The activated carbon-loaded nano zero-valent copper material prepared by the present invention still maintains a high adsorption performance in a high humidity environment, especially for the adsorption of toluene and hydrogen sulfide gases. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other embodiments can be obtained based on these drawings without paying creative work.

[0032] Figure 1 A scanning electron microscope image of an activated carbon-supported nano zero-valent copper material according to an embodiment of the present invention is shown;

[0033] Figure 2 An X-ray diffraction spectrum of an activated carbon-supported nano zero-valent copper material according to an embodiment of the present invention is shown;

[0034] Figure 3 The nitrogen adsorption-desorption curves and pore size distribution diagram of the activated carbon and an activated carbon-loaded nano zero-valent copper material according to the embodiment of the present invention are shown;

[0035] Figure 4 The activated carbon and the activated carbon loaded with nano zero-valent copper material according to the embodiment of the present invention are shown. 2 -TPD curve graph;

[0036] Figure 5 The adsorption penetration curve and adsorption capacity diagram of hydrogen sulfide by the activated carbon and an activated carbon-supported nano zero-valent copper material according to the embodiment of the present invention are shown;

[0037] Figure 6The adsorption penetration curve and adsorption capacity diagram of hydrogen sulfide by an activated carbon-supported nano zero-valent copper material under different relative humidity are shown in an embodiment of the present invention;

[0038] Figure 7 The adsorption penetration curve and adsorption capacity diagram of toluene by activated carbon and an activated carbon-loaded nano zero-valent copper material according to an embodiment of the present invention are shown;

[0039] Figure 8 The adsorption penetration curves and adsorption capacity diagrams of activated carbon and an activated carbon-loaded nano zero-valent copper material for toluene at different relative humidities are shown. DETAILED DESCRIPTION

[0040] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific embodiments in conjunction with the accompanying drawings.

[0041] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0042] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0043] The activated carbon-loaded nano zero-valent copper material provided by the present invention realizes the modification of the activated carbon by loading the nano zero-valent copper on the surface of the activated carbon and distributing it evenly, thereby enhancing the adsorption effect of the activated carbon on the malodorous gas. The preparation method of the modified activated carbon material comprises: firstly pre-treating the activated carbon, placing it in deionized water for ultrasonication to obtain a solid-liquid mixture, then simultaneously adding a copper sulfate solution and a potassium borohydride solution thereto, reacting until no obvious bubbles are generated in the system liquid, and then washing the modified activated carbon material several times and freeze-drying it to obtain the activated carbon-loaded nano zero-valent copper material, wherein the reaction process needs to be protected by argon gas.

[0044] Embodiment 1:

[0045] S1. Pretreatment of activated carbon

[0046] Grind 100g of activated carbon into powder, sieve it with an 8-mesh filter 5 times, screen out 10g of activated carbon with a particle size of 8 mesh, and add it to a sulfuric acid solution with a concentration of 0.01mol / L and soak it for 10 minutes. Take out the soaked activated carbon, wash it repeatedly with deionized water 3 times, dry it in a constant temperature drying oven, and seal it for future use.

[0047] Optionally, grind 100g of activated carbon into powder, sieve it with an 8-mesh filter for 5 times, screen out 10g of activated carbon with a particle size of 8 mesh, add it to a 5% dilute hydrochloric acid solution and soak it for 15 minutes, mix it on a shaker for 10 minutes, then boil it on an electric stove for 5 minutes, and wash it with deionized water until it is neutral. Then heat it on an electric stove until the activated carbon is nearly dry, and finally put it in an oven at 105°C for 10 hours, take it out and cool it to room temperature, and store it in a desiccator for use.

[0048] S2. Preparation of activated carbon-supported nano-zero-valent copper materials

[0049] At room temperature, 5.0 g of activated carbon powder (8 mesh) and deionized water were mixed in a four-necked flask and stirred thoroughly to obtain an activated carbon deionized water mixed solution. 2.3574 g of CuSO 4 ·5H 2 O and 5.0927 g KBH 4 Dissolve in deionized water and dilute to 100 ml, then add CuSO4 to the activated carbon deionized water mixed solution at a rate of 1.5 ml / min under argon atmosphere. 4 and KBH 4 The solution was stirred at a speed of 300r / min during the dropwise addition process to ensure the full progress of the reaction. When the reaction was not significantly bubbled, the product was first vigorously shaken and washed 5 times with deoxygenated water, and then washed twice with anhydrous ethanol. The product obtained after washing was pre-frozen in a freeze dryer at -60°C, and then dried in a vacuum freeze dryer to obtain an activated carbon-loaded nano-zero-valent copper material, denoted as AC@Cu0-1, and unmodified activated carbon, denoted as AC. After the product was taken out, it was stored in a vacuum drying environment at room temperature until the material was used for experiment or characterization.

[0050] Alternatively, a liquid phase reduction method is used to synthesize the product. 2.3574 g CuSO 4 ·5H 2 O, disperse it in a solution with a volume ratio of 1:2 of ethanol: water of 250ml. Add 5.0g activated carbon powder (8 mesh) to the mixture and ultrasonically treat it for 30min. 5.0927g sodium borohydride is dissolved in 50ml deionized water and slowly added to the mixture at a drop rate of 1.5ml / min, during which nitrogen is continuously introduced. After the addition is completed, continue to stir electrically for 60min. After stirring, wash three times with deionized water and three times with anhydrous ethanol. The product obtained after washing is pre-frozen in a freeze dryer at -60°C, and then dried in a vacuum freeze dryer to obtain an activated carbon-loaded nano zero-valent copper material.

[0051] Optional, pre-freeze:

[0052] The product solution obtained after repeated washing with anhydrous ethanol twice was atomized by a spray gun and then sprayed into -196°C liquid nitrogen for pre-freezing.

[0053] Pre-freezing treatment research:

[0054] In order to study the influence of pre-freezing rate and find the most suitable freezing medium and freezing method, four pre-freezing schemes were designed (see Table 1). Among the four schemes, the pre-freezing rates are: No. 1 > No. 2 > No. 3 > No. 4.

[0055] Table 1 Temperature and freezing method corresponding to different freezing media

[0056] serial number Freezing medium Freezing medium temperature Freezing method 1 Liquid nitrogen -196℃ spray 2 dry ice -78℃ spray 3 Low temperature refrigerator -78℃ overall 4 Freeze Dryer -60℃ overall

[0057] Results Analysis :

[0058] Compared with the preparation conditions of the solution precursor No. 1, the three groups of solution precursors No. 2, 3, and 4 have insufficient pre-freezing rates due to the different freezing methods or freezing media used, resulting in serious segregation of solute salts, which ultimately affects the adsorption performance of the product in a high humidity environment. In order to ensure that solute segregation does not occur during the formation of the precursor solution, liquid nitrogen is selected as the freezing medium and a spray pre-freezing method is adopted. The adsorption performance of modified activated carbon prepared by different freezing media and freezing methods for hydrogen sulfide is shown in Table 2. As can be seen from Table 2, the selection of liquid nitrogen as the freezing medium and the spray pre-freezing method greatly improve the adsorption performance of the product for hydrogen sulfide in a high humidity environment, and the adsorption capacity is as high as 181.80 mg / g. The adsorption performance of modified activated carbon prepared by different freezing media and freezing methods for toluene is shown in Table 3. As can be seen from Table 3, the selection of liquid nitrogen as the freezing medium and the spray pre-freezing method greatly improve the adsorption performance of the product for toluene in a high humidity environment, and the adsorption capacity is as high as 430.68 mg / g.

[0059] The AC@Cu0-1 prepared in Example 1 was subjected to scanning electron microscopy (SEM) analysis, and the results are as follows: Figure 1 As shown. A large amount of white granular substances can be seen in the pores of activated carbon, which indicates that zero-valent copper nanoparticles are formed in the pores of activated carbon. The average particle size of the nanoparticles is 100nm to 250nm.

[0060] AC@Cu0-1 prepared in Example 1 was subjected to X-ray diffraction (XRD) analysis, and the results are as follows: Figure 2 As shown in the figure, the characteristic peaks of zero-valent copper appear at 2θ=43.32°, 50.45° and 74.12°. This indicates that the metal crystals on the prepared modified activated carbon are mainly nano-zero-valent copper.

[0061] The unmodified activated carbon AC and the prepared AC@Cu0-1 in Example 1 were subjected to N 2 Adsorption-desorption analysis, the results are as follows Figure 3 As shown. The specific surface area of ​​unmodified activated carbon AC is 911m 2 / g, total pore volume is 0.35cm 3 / g, micropore volume is 0.285cm 3 / g; the specific surface area of ​​the prepared modified activated carbon AC@Cu0-1 is 820m 2 / g, total pore volume is 0.33cm 3 / g, micropore volume is 0.255cm 3 / g. It can be seen that when activated carbon is loaded with nano zero-valent copper, the specific surface area and pore volume of activated carbon are reduced, which is specifically manifested as a reduction in micropore volume. The nitrogen adsorption and desorption curves of activated carbon before and after loading nano zero-valent copper are both type I. Combined with the pore size distribution diagram, it can be seen that activated carbon AC and modified activated carbon AC@Cu0-1 are mainly micropores, and the loading of nano zero-valent copper has a significant effect on the micropore volume of activated carbon.

[0062] The unmodified activated carbon AC and the prepared AC@Cu0-1 in Example 1 were subjected to CO 2 -TPD analysis, the results are as follows Figure 4 As shown. Figure 4 It can be seen that no obvious CO was detected in activated carbon AC. 2 Desorption peak, the prepared modified activated carbon AC@Cu0-1 can detect 4 CO 2 This shows that the introduction of nano zero-valent copper is conducive to the formation of alkaline sites in the activated carbon skeleton and improves the adsorption capacity of hydrogen sulfide and toluene.

[0063] The activated carbon AC in Example 1 and the prepared nano zero-valent copper modified activated carbon AC@Cu0-1 were subjected to a dynamic adsorption penetration test for adsorbing typical malodorous gas hydrogen sulfide, and the steps are as follows:

[0064] In each experiment, 0.3g of activated carbon AC or prepared modified activated carbon AC@Cu0-1 was taken, loaded into a quartz tube adsorption column, and fixed with quartz wool. The experimental adsorption temperature was controlled at 20°C by a water bath. The total flow rate of the simulated odorous gas used was set to 100ml / min, which contained 1000ppm hydrogen sulfide, and nitrogen was used as the balance gas. After the gas was evenly mixed, the adsorption penetration experiment was started, and the hydrogen sulfide concentration at the outlet of the adsorption column was measured every 5 minutes. The hydrogen sulfide concentration was detected by a gas chromatograph (Shimadzu-14B).

[0065] The breakthrough adsorption curve and adsorption capacity are shown in Figure 5As shown in the figure, the activated carbon AC used in Example 1 quickly penetrated at the beginning of the experiment, and the adsorption capacity of hydrogen sulfide was only 13.57 mg / g. The activated carbon AC@Cu0-1 modified with nano-zero-valent copper showed excellent hydrogen sulfide adsorption performance, with penetration occurring at 170 min, and the adsorption capacity was significantly improved, reaching 112.48 mg / g.

[0066] The nano zero-valent copper modified activated carbon AC@Cu0-1 prepared in Example 1 was subjected to a dynamic adsorption penetration test for adsorbing typical malodorous gas hydrogen sulfide under different humidity conditions, and the steps were as follows:

[0067] In each experiment, 0.3g of the modified activated carbon AC@Cu0-1 prepared in Example 1 was taken, loaded into a quartz tube adsorption column, and fixed with quartz wool. The experimental adsorption temperature was controlled by a water bath to 20°C. The total flow rate of the simulated odorous gas used was set to 100ml / min, which contained 1000ppm of hydrogen sulfide. The relative humidity was controlled by adjusting the nitrogen flow rate of the gas branch of the deionized water bubbling bottle, and nitrogen was used as the balance gas. After the gas was evenly mixed, the adsorption penetration experiment was started, and the hydrogen sulfide concentration at the outlet of the adsorption column was measured every 5 minutes. The hydrogen sulfide concentration was detected by a gas chromatograph (Shimadzu-14B).

[0068] The breakthrough adsorption curve and adsorption capacity are shown in Figure 6 As shown, nano zero-valent copper modified activated carbon AC@Cu0-1 showed excellent hydrogen sulfide adsorption performance under different humidity conditions (see Table 2). When the relative humidity was 60%, the adsorption capacity of modified activated carbon AC@Cu0-1 for hydrogen sulfide reached 154.80 mg / g.

[0069] Table 2 Adsorption performance of modified activated carbon prepared by different freezing media and freezing methods for hydrogen sulfide

[0070] serial number Freezing medium Freezing medium temperature Freezing method Adsorption capacity 1 Liquid nitrogen -196℃ spray 181.80mg / g 2 dry ice -78℃ spray 160.08mg / g 3 Low temperature refrigerator -78℃ overall 158.57mg / g 4 Freeze Dryer -60℃ overall 154.80mg / g

[0071] The nano zero-valent copper modified activated carbon AC@Cu0-1 prepared in Example 1 was subjected to a dynamic adsorption penetration test for adsorbing typical malodorous gas toluene, and the steps were as follows:

[0072] In each experiment, 0.3g of activated carbon AC or prepared modified activated carbon AC@Cu0-1 was taken, loaded into a quartz tube adsorption column, and fixed with quartz wool. The experimental adsorption temperature was controlled at 20°C by a water bath. The total flow rate of the simulated odorous gas used was set to 100ml / min, containing 500ppm toluene, and nitrogen was used as the balance gas. After the gas was evenly mixed, the adsorption penetration experiment was started, and the toluene concentration at the outlet of the adsorption column was measured every 10 minutes. The toluene concentration was detected by a gas chromatograph (Agilent-6890N).

[0073] The breakthrough adsorption curve and adsorption capacity are shown in Figure 7 As shown in Table 3, the activated carbon AC used in Example 1 has good adsorption performance for toluene, and the adsorption capacity for toluene reaches 311.99 mg / g. The adsorption performance of activated carbon AC@Cu0-1 modified with nano-zero-valent copper for toluene is improved (see Table 3), and the adsorption capacity reaches 390.68 mg / g.

[0074] Table 3 Adsorption performance of modified activated carbon prepared by different freezing media and freezing methods for toluene

[0075]

[0076]

[0077] The nano zero-valent copper modified activated carbon AC@Cu0-1 prepared in Example 1 was subjected to a dynamic adsorption penetration test for adsorbing typical malodorous gas toluene under different humidity conditions, and the steps were as follows:

[0078] In each experiment, 0.3 g of the activated carbon AC in Example 1 or the prepared modified activated carbon AC@Cu0-1 was taken, loaded into a quartz tube adsorption column, and fixed with quartz wool. The experimental adsorption temperature was controlled by a water bath to 20 ° C. The total flow rate of the simulated odorous gas used was set to 100 ml / min, which contained 500 ppm toluene. The relative humidity was controlled by adjusting the nitrogen flow rate of the gas branch of the deionized water bubbling bottle, and nitrogen was used as the balance gas. After the gas was evenly mixed, the adsorption penetration experiment was started, and the toluene concentration at the outlet of the adsorption column was measured every 10 minutes. The toluene concentration was detected by a gas chromatograph (Agilent-6890N).

[0079] The breakthrough adsorption curve and adsorption capacity are shown in Figure 8 As shown in the figure, it can be clearly seen that with the increase of relative humidity, the adsorption performance of toluene by both the original activated carbon AC and the activated carbon AC@Cu0-1 modified with nano-zero-valent copper showed a significant downward trend. However, the adsorption performance of toluene by the modified activated carbon AC@Cu0-1 was significantly better than that of the original activated carbon under different relative humidity conditions.

[0080] Example 2

[0081] S1. Pretreatment of activated carbon:

[0082] Grind 100g of activated carbon into powder, sieve it with a 50-mesh filter 5 times, screen out 10g of activated carbon with a particle size of 50 mesh, and add it to a 0.5mol / L sulfuric acid solution and soak it for 20 minutes. Take out the soaked activated carbon, wash it repeatedly with deionized water 3 times, dry it in a constant temperature drying oven, and seal it for future use.

[0083] S2. Preparation of activated carbon-supported nano zero-valent copper materials:

[0084] At room temperature, 5.0 g of activated carbon powder (50 mesh) and deionized water were mixed in a four-necked flask and stirred thoroughly to obtain an activated carbon deionized water mixed solution. 1.5716 g of CuSO 4 ·5H 2 O and 3.3951 g KBH 4 Dissolve in deionized water and dilute to 250 ml, then add CuSO4 to the activated carbon deionized water mixed solution at a rate of 2 ml / min under argon atmosphere. 4 and KBH 4 The solution was stirred at a speed of 350r / min during the dropwise addition process to ensure the full progress of the reaction. When the reaction was not significantly bubbled, the product was first vigorously shaken and washed 5 times with deoxygenated water, and then washed twice with anhydrous ethanol. The product obtained after washing was pre-frozen in a freeze dryer at -60°C, and then dried in a vacuum freeze dryer to obtain an activated carbon-loaded nano zero-valent copper material.

[0085] Results Analysis :(Please explain the results of this example)

[0086] The modified activated carbon prepared by the method is loaded with 10 wt.% zero-valent copper, and its cost and adsorption performance are between 20 wt.% and 5 wt.% loading ratios.

[0087] Example 3

[0088] S1. Pretreatment of activated carbon

[0089] Grind 100g of activated carbon into powder, sieve it with a 25-mesh filter 5 times, screen out 10g of activated carbon with a particle size of 25 mesh, and add it to a 0.25mol / L sulfuric acid solution and soak it for 15 minutes. Take out the soaked activated carbon, wash it repeatedly with deionized water 3 times, dry it in a constant temperature drying oven, and seal it for later use.

[0090] S2. Preparation of activated carbon-supported nano-zero-valent copper materials

[0091] At room temperature, 5.0 g of activated carbon powder (25 mesh) and deionized water were mixed in a four-necked flask and stirred thoroughly to obtain an activated carbon deionized water mixed solution. 0.7858 g of CuSO 4 ·5H 2 O and 1.6976 g KBH 4 Dissolve in deionized water and dilute to 100 ml, then add CuSO4 to the activated carbon deionized water mixed solution at a rate of 2 ml / min under argon atmosphere. 4 and KBH 4 The solution was stirred at a speed of 300 r / min during the dropwise addition process to ensure the full progress of the reaction. When the reaction was not significantly bubbled, the product was first vigorously shaken and washed 5 times with deoxygenated water, and then washed twice with anhydrous ethanol. The product obtained after washing was pre-frozen in a freeze dryer at -60°C, and then dried in a vacuum freeze dryer to obtain an activated carbon-loaded nano-zero-valent copper material.

[0092] Results Analysis :

[0093] The modified activated carbon prepared by this method is loaded with 5wt.% zero-valent copper and has the lowest cost, but its adsorption performance is weaker than that of the modified activated carbon loaded with 10wt.% and 20wt.%.

[0094] Based on the results of the above examples, the activated carbon modified with zero-valent copper has a significant effect on the typical malodorous gas (H 2 The adsorption performance of modified activated carbon AC@Cu0-1 for hydrogen sulfide reached a maximum value of 154.80 mg / g at a relative humidity of 60%, and the adsorption capacity for toluene reached a maximum value of 390.68 mg / g at a relative humidity of 0%.

Claims

1. A method for preparing an activated carbon-supported nano zero-valent copper material, characterized in that: include: S1, pretreating activated carbon with sulfuric acid solution and deionized water to obtain pretreated activated carbon powder; S2, stirring the pretreated activated carbon powder and deionized water to obtain an activated carbon deionized water mixed solution; S3, using CuSO4·5H2O, KBH4 and deionized water, stirring the activated carbon deionized water mixed solution to obtain an activated carbon zero-valent copper mixed solution; S4, using deoxygenated water, anhydrous ethanol and a vacuum freeze dryer, the activated carbon zero-valent copper mixed solution is washed, pre-frozen and dried in sequence to obtain the activated carbon-loaded nano zero-valent copper material.

2. The method for preparing the activated carbon-supported nano zero-valent copper material according to claim 1, characterized in that: The method of pretreating the activated carbon with a sulfuric acid solution and drying the pretreated activated carbon powder comprises: S11, grinding the activated carbon into powder, and adding the powder into a sulfuric acid solution for soaking treatment to obtain soaked activated carbon; S12, using deionized water to wash and dry the soaked activated carbon to obtain pretreated activated carbon powder.

3. The method for preparing the activated carbon-supported nano zero-valent copper material according to claim 2, characterized in that: The activated carbon powder has a mesh size of 8 to 50.

4. The method for preparing the activated carbon-supported nano zero-valent copper material according to claim 2, characterized in that: The concentration of the sulfuric acid solution is 0.01 mol / L to 0.5 mol / L; and the soaking time is 10 min to 20 min.

5. The method for preparing the activated carbon-supported nano zero-valent copper material according to claim 1, characterized in that: The method comprises: stirring the activated carbon deionized water mixed solution by using CuSO4·5H2O, KBH4, deionized water and a peristaltic pump to obtain an activated carbon zero-valent copper mixed solution. S31, adding CuSO4·5H2O and KBH4 into deionized water and adjusting the volume to 100 ml to 250 ml to obtain a CuSO4·5H2O-KBH4 mixed solution; S32, under room temperature and oxygen-free conditions, using a peristaltic pump, dropwise adding the CuSO4·5H2O-KBH4 mixed solution into the activated carbon deionized water mixed solution, and stirring the mixture to obtain an activated carbon zero-valent copper mixed solution.

6. The method for preparing the activated carbon-supported nano zero-valent copper material according to claim 5, characterized in that: The molar ratio of KBH4 to CuSO4·5H2O is 3:1-6:1; the dropping speed of the peristaltic pump is 1.5ml / min-2ml / min; and the stirring speed is 300r / min-350r / min.

7. The method for preparing the activated carbon-supported nano zero-valent copper material according to claim 1, characterized in that: The activated carbon-supported nano-zero-valent copper material is obtained by washing, prefreezing, and drying the activated carbon-supported nano-zero-valent copper mixed solution in sequence using deoxygenated water, anhydrous ethanol, and a vacuum freeze dryer, comprising: S41, using deoxygenated water and anhydrous ethanol to wash the activated carbon-supported nano zero-valent copper material in sequence to obtain a washed activated carbon-supported nano zero-valent copper material; S42, pre-freezing the washed activated carbon-loaded nano zero-valent copper material to obtain a pre-frozen activated carbon-loaded nano zero-valent copper material; S43, using a vacuum freeze dryer to dry the pre-frozen activated carbon-loaded nano zero-valent copper material to obtain the activated carbon-loaded nano zero-valent copper material.

8. The method for preparing the activated carbon-supported nano zero-valent copper material according to claim 7, characterized in that: The mass loading ratio of the nano-zero-valent copper in the activated carbon-loaded nano-zero-valent copper material on the activated carbon is 5wt.% to 20wt.%; the average particle size of the loaded nano-zero-valent copper is 100nm to 250nm; Preferably, the mass loading ratio of nano zero-valent copper on the activated carbon is 5wt.% to 15wt.%.

9. An application of activated carbon-supported nano zero-valent copper material, characterized in that: Application of activated carbon-loaded nano zero-valent copper material prepared by the preparation method described in any one of claims 1 to 8 in adsorbing malodorous gases under high humidity conditions.

10. The use of activated carbon-supported nano zero-valent copper material according to claim 9, characterized in that: The high humidity is 0-80%; the malodorous gas is one or two of hydrogen sulfide and toluene.